Current-fed Step-up DC/DC Converter for Fuel Cell Applications with Active Overvoltage Clamping - Andreiciks, Aleksandrs; Steiks, Ingars; Krievs, Oskars (Electrical, Control and Communication Engineering, 2010)
In order to use hydrogen fuel cells in domestic applications either as main power supply or backup source, their low DC output voltage has to be matched to the level and frequency of the utility grid AC voltage. Such power converter systems usually consist of a DC-DC converter and a DC-AC inverter. A double inductor step-up push-pull converter is investigated in this paper, presenting simulation and experimental results for passive and active overvoltage clamping. The prototype of the investigated converter is elaborated for 1200 W power to match the rated power of the proton exchange membrane (PEM) fuel cell located in hydrogen fuel cell research laboratory.